The Effect of Training, Competence and Motivation on Employee Productivity with Work Engagement as an Intervening Variable - Prabaswara, Tsaqif; Suhardi, Suhardi; Amin, Mat; Sofyan, Agus (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyse the effect of exercise, competition, and motivation on work engagement and employee performance, with work engagement as a mediating variable in employees of the Pangkal Pinang City Health Office. The research method used is quantitative with the Structural Equation Modelling-Partial Least Squares (SEM-PLS) approach, involving 112 purposively selected respondents. The analysis results show that specifically, competition is the factor that has the most significant effect on work engagement and employee performance, followed by motivation with a moderate effect, while exercise shows the least effect. Work engagement was shown to partially mediate the relationship between motivation and competition on employee performance. These findings confirm the importance of human resource development strategies that not only focus on training but also on creating a healthy competitive environment, increasing motivation, and strengthening work engagement to encourage optimal employee performance. This study recommends the need to develop an integrated organisational programme to improve employee engagement and performance, as well as further research by expanding the variables and methods used.